Role of Epstein-Barr Virus Reactivation in Malaria Severity - Chatue, Ide Armelle Djuidje; Netongo, Palmer Masumbe; Kamdem, Severin Donald; Franklin, Maloba; Lesly, Ngum Ngum; Djogang, Anselme Michel Yawat; Kwetché, Pierre René Fotsing; Nyegue, Maximilienne Ascension (Archives of Clinical and Biomedical Research, 2022)
Epstein-Barr Virus (EBV) known as human gammaherpesvirus is latently present in more than 95% of the world adult population. The virus undergoes lytic replication and latent cycle to insure its spread and the episomal persistence of the viral genome respectively. Under certain conditions that dysregulate the host immune system, latent EBV infection reactivates. EBV reactivation has been involved in the pathogenesis of a variety of autoimmune diseases and cancers. Many studies describe the association between Epstein-Barr virus reactivation and malaria severity. It is suggested that the reactivation of EBV infection (lytic replication) impairs the immune response to malaria, exacerbates its pathogenesis, and increases the frequency and susceptibility to severe malaria. However, the immunological mechanisms are not clear. A thorough understanding of the specific role of EBV reactivation in the severity of malaria, is crucial to the development of effective vaccine. In this review, we provide a summary of the impact of Epstein-Barr Virus reactivation on malaria in the current scientific literature.